BUILDING STUDENTS’ CHARACTER ON CIVIC EDUCATION THROUGH LOCAL WISDOM OF SADRANAN - Abdul Rozaq Sholeh; Siti Sutarmi Fadhilah; Tri Murwaningsih (AL-ASASIYYA: Journal Of Basic Education, 2019)
Sadranan is a form of cultural assimilation of Hinduism and Buddhism by Islam whose activities are clean villages and visiting residents' homes. In some places Sadranan traditions have different forms of ceremonies. Some Sadranan in other places are called "clean villages". These activities include cleaning roads, markets, graveyards, village halls and fields. In this activity the community becomes one and jointly cleanses the place. The aim of this study was to determine how to build the students’ character through cultural wisdom Sadranan at SD N 2 Ketaon. The method used in this study is descriptive qulitative. The researcher was conducted the reseach with collecting the data by observation, interview and documentation. The result of the research is the researcher can found the values of the Sadranan that are respecting to others, harmony, cooperation, hard work, gratitude, religious, and protecting the environment. The conclusion of this study is that students can show the better characters.